Alternative splicing and cycling kinetics of myosin change during hypertrophy of human smooth muscle cells - Morano, Ingo; Köhlen, Stefan; Haase, Hannelore; Erb, Gunter; Baltas, Leonidas G.; Rimbach, Stefan; Wallwiener, Diethelm; Bastert, Gunther (Journal of cellular biochemistry, 1997)
We investigated in vivo expression of myosin heavy chain (MHC) isoforms, 17 kDa myosin light chain (MLC17), and phosphorylation of the 20 kDa MLC (MLC20) as well as mechanical performance of chemically skinned fibers of normal and hypertrophied smooth muscle (SM) of human myometrium. According to their immunological reactivity, we identified three MHC isoenzymes in the human myometrium: two SM-MHC (SM1 with 204 kDa and SM2 with 200 kDa), and one non-muscle specific MHC (NM with 196 kDa). No cross-reactivity was detected with an antibody raised against a peptide corresponding to a seven amino acid insert at the 25K/50K junction of the myosin head (a-25K/50K) in both normal and hypertrophied myometrium. In contrast, SM-MHC of human myomatous tissue strongly reacted with a-25K/50K. Expression of SM1/SM2/NM (%) in normal myometrium was 31.7/34.7/33.6 and 35.1/40.9/24 in hypertrophied myometrium. The increased SM2 and decreased NM expression in the hypertrophied state was statistically significant (P < 0.05). MHC isoform distribution in myomatous tissue was similar to normal myometrium (35.3/35.3/29.4). In vivo expression of MLC17a increased from 25.5% in normal to 44.2% in hypertrophied (P < 0.001) myometrium. Phosphorylation levels of MLC20 upon maximal Ca20-calmodulin activation of skinned myometrial fibers were the same in normal and hypertrophied myometrial fibers. Maximal force of isometric contraction of skinned fibers (pCa 4.5, slack-length) was 2.85 mN/mm2 and 5.6 mN/mm2 in the normal and hypertrophied state, respectively (P < 0.001). Apparent maximal shortening velocity (Vmaxapp, extrapolated from the force-velocity relation) of myometrium rose from 0.13 muscle length s 1 (ML/s) in normal to 0.24 ML/s in hypertrophied fibers (P < 0.001). J. Cell. Biochem, 64:171-181. © 1997 Wiley-Liss, Inc.
Elektronische Reproduktion der Druck-Ausgabe 7. Dezember 1998
Gesehen am 18.03.2024